Business survival rates across the urban–rural divide. Issue 1 (1st January 2017) - Deller, Steven C.; Conroy, Tessa
Abstract: Scholars and practitioners have concluded that entrepreneurship and small business development is central to community economic development. Often times community members, including elected officials, are skeptical of the importance of new and small firms due to their seemingly high failure rate. In this study we use the National Establishment Time Series (NETS) database of US establishments survival rate of new firms in each US county. For each county, we identify the number of new firms born in each year and calculate their survival rate as the share of firms from each cohort still operating five years later. We then explore how survival rates change over a simple urban–rural spectrum from 1990 to 2007. As expected, survival rates vary significantly by birth year, and new businesses in rural communities tend to have higher survival rates than those in urban communities. We close the study with a discussion of specific policy options.